2016
DOI: 10.3856/vol44-issue5-fulltext-9
|View full text |Cite
|
Sign up to set email alerts
|

Protein hydrolysate waste of whitemouth croaker (Micropogonias furnieri) as a way of adding value to fish and reducing the environmental liabilities of the fishing industry

Abstract: ABSTRACT.As an alternative use of natural marine resources, processing waste from whitemouth croaker was used as raw material for the production of fish protein hydrolysate (FPH). The biometric characterization of the raw material was determined, and the optimal conditions of the protease established using DH (degree of hydrolysis) as the criterion. Bromatological analyses were performed according to AOAC methods. The DH were determined by the TCA (trichloroacetic acid) method and expressed as a percentage of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…This pattern may be related to the fact that HPHs produced with 1% w/v enzyme were not extensively hydrolyzed (reaching a maximum of 12.7% DH), so that part of the protein content in herring muscle was not solubilized, being subsequently removed in the precipitated fraction during the centrifugation process. Other authors have reported ranges of percent protein content (78-80%) in fish muscle hydrolysates that are consistent with the results obtained in this study (Oliveira de Amorim et al, 2016;Ben Slama-Ben Salem et al 2017). Considering the high protein content in HPHs, these show potential for use as a nutritional supplement in the preparation of animal feed, mainly for carnivorous species with a high protein demand.…”
Section: Proximate Composition Of Raw Materials and Herring Muscle Hysupporting
confidence: 91%
“…This pattern may be related to the fact that HPHs produced with 1% w/v enzyme were not extensively hydrolyzed (reaching a maximum of 12.7% DH), so that part of the protein content in herring muscle was not solubilized, being subsequently removed in the precipitated fraction during the centrifugation process. Other authors have reported ranges of percent protein content (78-80%) in fish muscle hydrolysates that are consistent with the results obtained in this study (Oliveira de Amorim et al, 2016;Ben Slama-Ben Salem et al 2017). Considering the high protein content in HPHs, these show potential for use as a nutritional supplement in the preparation of animal feed, mainly for carnivorous species with a high protein demand.…”
Section: Proximate Composition Of Raw Materials and Herring Muscle Hysupporting
confidence: 91%
“…The fat content of parrotfish head FPH was lower than the FPH from croaker fish head waste (5.1 ± 4.0%) (Amorim et al, 2016) and commercial FPH (19–22%) (International Quality Ingredients (IQI), 2005). The low-fat content of parrotfish head FPH was due to the low-fat content in fish head raw materials (3.92%).…”
Section: Discussionmentioning
confidence: 95%
“…Based on its protein content, FPH from parrotfish heads could be classified as a type B hydrolysate. The fat content of parrotfish head FPH was lower than the FPH from croaker fish head waste (5.1±4.0%) (Amorim et al, 2016) and commercial FPH (19-22%) (IQI, 2005). The low-fat content of parrotfish head FPH was due to the low-fat content in fish head raw materials (3.92%).…”
Section: Discussionmentioning
confidence: 79%